Quantum-size-effect accommodation of gold clusters with altered fluorescence of dyes. Issue 39 (31st March 2015) - Liu, Xianhu; Wu, Yishi; Li, Shuanghao; Zhao, Yan; Yuan, Chengqian; Jia, Meiye; Luo, Zhixun; Fu, Hongbing; Yao, Jiannian
Abstract : Quantum-size-effect accommodation towards Au25 nanoclusters is demonstrated with tunable fluorescence quenching and enhancement of analyte dyes. Abstract : We have synthesized monodispersed Au25 nanoclusters (NCs) stabilized with eco-friendly glutathione and report here an insight into their interactions with dye molecules. In the presence of such gold NCs, consistent fluorescence quenching was observed for all the dye molecules that we examined in this study regardless of their maximum emission wavelengths. The steady-state and time-resolved spectroscopic results demonstrate that the weakened luminance is associated with the protective ligand pertaining to a static quenching mechanism. Having expounded this issue, we further employed proper laser irradiation enabling dissociation of Au25 (SG)18 so as to attain a transformation of nonplasmonic NCs into plasmonic gold nanoparticles (NPs) via photo-assisted aggregation of the dissociated gold clusters. As a result, emission enhancement for these dyes was observed, which is largely attributed to the local electromagnetic field enhancement of gold NPs. The alternation of fluorescence quenching to emission enhancement reflects an accommodation of quantum size effects upon the ligand-stabilized gold clusters.